CONDITION OF DONATION IN BLOOD SERVICE - Kamal Tashtemirov; Sagit Imangazinov; Olga Tashtemirova (European Scientific Journal, ESJ, 2014)
There has been a monitoring of donation in Pavlodar region. It has been established that over the years of observation there was a significant change both in the number and structure of the donors in Pavlodar region: number of donors seems to increase, similar to the growth of the total number of donors, the number of donors per thousand people has increased. The number of primary donors has decreased and there are unsteady requests for blood donation. Growth of free donations is conditioned upon donating relatives of recipients. There is a tendency to a decrease in the share of male donors and increase in the share of female donors. There is a steady increase in the share of donors from 30 to 39 years old, workers and employees with a predominance of urban residents.